Aerobic and resistance exercise in systemic sclerosis: State of the art. (5th April 2017) - de Oliveira, Natália Cristina; Portes, Leslie Andrews; Pettersson, Henrik; Alexanderson, Helene; Boström, Carina
Abstract: Introduction: Patients with systemic sclerosis (SSc) experience reduced exercise capacity and muscle strength compared with healthy subjects. There are also indications of reduced levels of physical activity. Objective: To present the current knowledge of physical exercise in SSc. Results: Most studies presently available [three case studies, one single subject experimental design, one study comparing patients with healthy controls, one quasi experimental design (pre–post), two clinical trials and two random controlled trials] have included small samples of patients, mostly composed of patients with and without pulmonary involvement. It seems that patients with SSc without pulmonary involvement are able to perform and benefit from aerobic exercises of at least moderate intensity. Exercise tolerance, aerobic capacity, walking distance, muscle strength and muscle function as well as health‐related quality of life (HRQL) have been found to be improved after participation in programmes including aerobic exercise and aerobic exercise combined with resistance exercises. Improvements seem to be only partially retained at follow up. Patients with pulmonary involvement may also experience improved muscle strength, physical and aerobic capacity, as well as HRQL following exercise. Conclusions: Patients with SSc without pulmonary involvement can be recommended to be as physically active as the general population. Patients with mild pulmonary involvement can be recommended to be physically active by engaging in exercises of moderate intensity and to participate in moderate‐load resistance exercises. Health professionals should inform patients with SSc about the importance of physical activity and avoidance of a sedentary lifestyle.